Analisis Tingkat Kebangkrutan Model Altman, Foster, dan Springate Pada Perusahaan Property and Real Estate Go Public di Bursa Efek Indonesia (Periode 2008-2011) - Wibisono, Rizky Teguh; Dp, Emrinaldi Nur; ', Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study purpose to determine whether there are differences among Altman model, Foster model and Springate model in forecasting bankruptcy, and to find out which bankruptcy prediction models has the most excellent implementation on company property and real estate in Indonesia. Comparison of those three models were made by analyzing the accuracy of each model, by using the real condition of a company's net income. The data used in the form of annual financial statements published by the companies in the Indonesia Stock Exchange.The population used is a property and real estate companies listed on the Indonesia Stock Exchange period 2008-2011. The sampling technique is porposive sampling with a total sample obtained by 18 companies. Paried sample t-test used to examine differences among Altman, Foster and Springate models in predicting bankruptcy.The result from this research showed that there is no statistical difference between Altman and Foster models in 2008-2010, but it occurs in 2011. Next, ther is a statistical difference between Altman and Springate models in 2008-2011, but it is not going on between Foster and Springate models. So, Springate model is the best way in a prediction of bankruptcy.Keywords: Bankruptcy, PredictionModels, Financial Ratios, Financial Statement